Should Renal Inflammation Be Targeted While Treating Hypertension? - Chaudhari, Sarika; Pham, Grace S.; Brooks, Calvin D.; Dinh, Viet Q.; Young-Stubbs, Cassandra M.; Shimoura, Caroline G.; Mathis, Keisa W. (Frontiers in Physiology, 2022)
Despite extensive research and a plethora of therapeutic options, hypertension continues to be a global burden. Understanding of the pathological roles of known and underexplored cellular and molecular pathways in the development and maintenance of hypertension is critical in order to advance the field. Immune system overactivation and inflammation in the kidneys have been proposed as alternative mechanisms of hypertension, and resistant hypertension. Consideration of the pathophysiology of hypertension in chronic inflammatory conditions such as autoimmune diseases, in which patients present with autoimmune-mediated kidney inflammation as well as hypertension, may reveal possible contributors and novel therapeutic targets. In this review, we 1) summarize current therapies used to control blood pressure and their known effects on inflammation; 2) provide evidence on the need to target renal inflammation, specifically, especially when first-line and combinatory treatment efforts fail; and 3) discuss the efficacy of therapies used to treat autoimmune-induced hypertension. We aim to elucidate the potential of targeting renal inflammation in certain subsets of patients resistant to current therapies.